Clinical, radiological and microbiological corroboration to assess the role of endotracheal aspirate in diagnosing ventilator-associated pneumonia in an intensive care unit of a tertiary care hospital, India - Mukhopadhyay, Chiranjay; Krishna, Sushma; Shenoy, Anita; Prakashini, K (International Journal of Infection Control, 2009)
Early and accurate diagnosis and follow up of VAP varies considerably with the clinical, radiological and microbiological criteria employed. This study was aimed to correlate clinico-radiological findings with microscopy and quantitative culture of consecutive ETA from 50 mechanically ventilated patients along with the antibiogram and risk factor assessment. The prospective observational study in MICU revealed the incidence of VAP to be 42% with a rate of 116/1000 ventilator days. 8 had early onset and 13 late onset VAP, with no age or sex significant preponderance. The attributable mortality rate was 61.9% which rose with duration of stay. The important independent risk factors were multi-organ failure, re-intubation and pleural effusion. The most commonly isolated organisms were multidrug resistant Acinetobacter baumannii (76%) and Pseudomonas aeruginosa (42%). All enterobacterial isolates were ESBL producing and all S. aureus isolates were methicillin resistant. In 66%, colonization on day 1 resulted in development of VAP on day 4. Gram stain findings had a significant correlation with the quantitative culture of ETA, which by itself showed a significantly progressive increase in specificity in diagnosing VAP on day 7. The strength of association between CPIS scoring, the microbiological findings and the clinical diagnosis was found to be strong. This study emphasizes that Gram stain and quantitative culture of ETA can be considered useful for the diagnosis of VAP and a combined clinical, radiological and microbiological approach can be successful in the management and further follow up of VAP.